Intergenerational social mobility and the ambivalent role of higher education: a systematic review - Mendoza Marín, Reynaldo Justo; Garay Canales, Henry Bernardo; Aldana Cáceres, Alejandro; Callupe Cueva, Paulo César (International Journal of Evaluation and Research in Education (IJERE), 2025)
University education has historically been considered a means of upward social mobility. However, recent studies question this equalizing role, finding substantial differences in the “rewards” it represents according to social class. Thus, the objective of this research is to analyze the relationship between having university studies and experiencing intergenerational social mobility in today’s world. For this purpose, a systematic review of the literature was carried out under a qualitative approach. A bibliographic search was carried out in academic data bases of renowned prestige, such as Scopus, Web of Science, and ERIC. Specific search terms such as “intergenerational social mobility”, “university education” and “inequality” were also used, considering the period between 2014 and 2024. A total of 28 articles were analyzed. The findings show that, while graduates with professional parents effectively capitalize on the educational credential, those who come first in their families face more barriers to translating the degree into occupational mobility. Socioeconomic origin also delimits trajectories within universities and impacts on dropout, graduation, and differentiated academic performance. Consequently, the magnitude of this mobility varies significantly by social origin, with graduates from professional or academic families demonstrating a markedly greater ability to leverage their educational credentials in the labor market.